2022
DOI: 10.1182/bloodadvances.2021005492
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated donor α/β T cell– and B cell–depleted HSCT for the treatment of pediatric acute leukemia

Abstract: Unrelated donor (URD) hematopoietic stem cell transplant (HSCT) is associated with an increased risk of severe GVHD. TCRαβ/CD19 depletion may reduce this risk, while maintaining graft-versus-leukemia. Outcome data with TCRαβ/CD19 depletion generally describes haploidentical donors, with relatively few URDs. We hypothesized that TCRαβ/CD19-depletion would attenuate the risks of GVHD and relapse for URD HSCT. Sixty pediatric and young adult (YA) patients with hematologic malignancies who lacked a matched-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…As expected with αß TB cell depletion, the rates of viral reactivation were higher than matched transplant approaches. Those reporting viral reactivations reported consistent rates of 40-65% of patients experiencing reactivations, with 20-65% reactivating CMV, 0-44% EBV, up to 57% adenovirus, 21% HHV6, and 23% BK virus ( 129 134 , 136 142 ). A large retrospective review showed the incidence of CMV and EBV reactivation were 53% and 33% respectively after αß TB cell depletion and associated with aGVHD ( 147 ).…”
Section: Alpha/beta T Cell/b Cell Depletion (αßTb Depletion)mentioning
confidence: 87%
See 3 more Smart Citations
“…As expected with αß TB cell depletion, the rates of viral reactivation were higher than matched transplant approaches. Those reporting viral reactivations reported consistent rates of 40-65% of patients experiencing reactivations, with 20-65% reactivating CMV, 0-44% EBV, up to 57% adenovirus, 21% HHV6, and 23% BK virus ( 129 134 , 136 142 ). A large retrospective review showed the incidence of CMV and EBV reactivation were 53% and 33% respectively after αß TB cell depletion and associated with aGVHD ( 147 ).…”
Section: Alpha/beta T Cell/b Cell Depletion (αßTb Depletion)mentioning
confidence: 87%
“…Overall, this has been observed with median rates of grade II-IV aGVHD of 18% (ranging from 11-28%), and cGVHD of 8% (range 0-30%), with 0-21% experiencing extensive cGVHD ( 129 144 ). Notably, most of these studies utilized ATG, which has reduced aGVHD (see above), and not surprisingly, in one study in which ATG was removed, the observed rates of aGVHD were increased ( 136 ). The relapse rates ranged from 18-30% for those utilizing αßTB depleted HCT for the treatment of hematologic malignancies, comparable overall to other approaches ( 129 , 135 137 , 141 , 143 , 144 ).…”
Section: Alpha/beta T Cell/b Cell Depletion (αßTb Depletion)mentioning
confidence: 99%
See 2 more Smart Citations
“…The pediatric BMT community has expressed general concern regarding the CuI of relapse using PTCy. The CuI of relapse reported in published studies using haploidentical donors, MUDs, cord, and matched sibling donors has ranged from 12% to 70% 15 , 44 , 45 , 46 , 51 , 56 , 57 , 58 , 59 , 60 with pre-BMT MRD positivity and a high DRI associated with a higher incidence of relapse. The CuI of relapse of 32% and 36% at 1 and 2 years, respectively, in our small, multicenter study, with lower but not statistically significant CuI of relapse in MRD negative and low-intermediate DRI patients, is directly comparable with that reported in the pediatric BMT published literature and does not support that haplo-BMT with PTCy is inferior.…”
Section: Discussionmentioning
confidence: 99%